Competencias docentes para la inclusión de niños con necesidades educativas especiales - Arboleda Quinde, Maida Elizabeth (2021)
This research work is focused on TEACHING COMPETENCES FOR THE INCLUSION OF CHILDREN WITH SPECIAL EDUCATIONAL NEEDS OF THE SECOND YEAR OF BASIC EDUCATION OF THE EDUCATIONAL UNIT "CLAIRE BUCARAM DE AIVAS", it has the purpose of developing new and better competences that, carry out the inclusion of children with special educational needs. This research shows that some teachers are not prepared and lack the necessary tools that favor the teaching-learning process. It should be noted that some children do not feel motivated and included in the classroom, it is difficult for them to relate to their peers and they lack communication with the teacher. Therefore, the objective of the research is to provide tools that facilitate work with children who present some type of need. From this perspective, the research considers the mixed approach to carry out the study of the problem…..